A comparison of computational fluid dynamics predicted initial liquid penetration using rate of injection profiles generated using two different measurement techniques. (February 2019) - Ge, Haiwen; Johnson, Jaclyn E; Krishnamoorthy, Hari; Lee, Seong-Young; Naber, Jeffrey D; Robarge, Nan; Kurtz, Eric
The rate of injection profile is a key parameter describing the fuel injection process for diesel injection. It is also an essential input parameter for computational fluid dynamics simulations of spray flows. In the present work, rate of injection profiles of a multi-hole diesel injector were measured using the Zeuch method and the momentum flux method. The rate of injection profiles measured by the momentum flux method had a faster rise in rate of injection during the initial ramp-up phase than with the Zeuch method. The measured rate of injection profiles were applied in three-dimensional computational fluid dynamics simulations of diesel sprays under non-vaporizing and vaporizing conditions with sweeps in injection pressure, bulk charge gas density, and bulk charge gas temperature. Analytical results were compared against experimental data for liquid penetration generated under those conditions. Computational fluid dynamics results with the rate of injection profile measured by the Zeuch method under-predict liquid penetration during the initial ramp-up phase, while computational fluid dynamics results with the rate of injection profiles measured by the momentum flux method showed much better agreement with the experimental data of liquid length and penetration. This suggests that current computational fluid dynamics spray models may be able to more accurately model transient liquid penetration when using the velocity profile developed from momentum flux measurements. Further study is needed to evaluate how computational fluid dynamics predictions of combustion and emissions of affected when using these two rate of injection profiles.